2021
DOI: 10.1128/msphere.01185-20
|View full text |Cite
|
Sign up to set email alerts
|

Specific Norovirus Interaction with Lewis x and Lewis a on Human Intestinal Inflammatory Mucosa during Refractory Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and ulcerative colitis (UC), is related to immunological and microbial factors, with the possible implication of enteric viruses. We characterized the interaction between human noroviruses (HuNoVs) and blood group antigens in refractory CD and UC using HuNoV virus-like particles (VLPs) and histological tissues. Immunohistochemistry was conducted on inflammatory tissue samples from the small intestine, colon, and rectum in 15 CD and 9 UC pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Importantly, increased CD44v6 expression in IBD correlates with increased inflammatory infiltrates and with increased mucosal tissue damage 42 . More recent immunohistological and liquid chromatography mass spectrometric glycomics analyses have demonstrated upregulated expression of sialylated Lewis family O-glycans on epithelial CD44v6 and on Muc2 in inflamed human and murine colonic mucosa 33 , 34 , 82 85 . Furthermore, recent functional studies have shown that antibody targeting of specific sialyl-Lewis glycans on epithelial CD44v6 blocks human neutrophil transepithelial migration (TEpM), protects against DSS-induced colitis in vivo and promotes epithelial wound closure following colonic injury 33 , 34 , 86 .…”
Section: Inflammation-induced Alterations In Glycosylation In the Intestinal Epithelium Are Linked To Pathobiology Of Mucosal Diseasementioning
confidence: 99%
“…Importantly, increased CD44v6 expression in IBD correlates with increased inflammatory infiltrates and with increased mucosal tissue damage 42 . More recent immunohistological and liquid chromatography mass spectrometric glycomics analyses have demonstrated upregulated expression of sialylated Lewis family O-glycans on epithelial CD44v6 and on Muc2 in inflamed human and murine colonic mucosa 33 , 34 , 82 85 . Furthermore, recent functional studies have shown that antibody targeting of specific sialyl-Lewis glycans on epithelial CD44v6 blocks human neutrophil transepithelial migration (TEpM), protects against DSS-induced colitis in vivo and promotes epithelial wound closure following colonic injury 33 , 34 , 86 .…”
Section: Inflammation-induced Alterations In Glycosylation In the Intestinal Epithelium Are Linked To Pathobiology Of Mucosal Diseasementioning
confidence: 99%
“… b The values are given in resonance unit (RU). c For duodenal tissues, the intensity of the signal is graded based upon a positive control from a previous study ( Tarris et al, 2021 ). +++, strong; ++, intermediate; +, low/focal; and −, negative.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were taken during routine surgical procedures performed at the University Hospital of Dijon (France). The detection of A, H, and Le b antigens and the experimental conditions for VLP binding on histological sections were described previously using VLPs diluted at 5 μg/ml ( Marionneau et al, 2002 ; Tarris et al, 2019 ); ( Tarris et al, 2021 ). Attached VLPs were detected with GII.17-specific polyclonal serum described above.…”
Section: Methodsmentioning
confidence: 99%
“…Four µm-thick microtome sections were cut from FFPE samples. Sections were deparaffinized, quenched and pretreated for endogenous peroxidase inhibition, as previously described (15). Five µg/ml of in-house purified GII.4, GII.3 or GII.17 VLP diluted in PBS with BSA 1% were incubated on each slide overnight at 4°C.…”
Section: Histological Analysis and Immunodetection On Tissue Samplesmentioning
confidence: 99%
“…During flare ups, marked structural alterations are seen in the inflamed mucosae (16). Blood group ABO(H) antigens are usually not displayed at the surface of inflammatory and regenerative colonic and rectal mucosa, whereas a strong expression of Sialyl-Le a (sLe a ) (also known as CA19.9) and to a lesser extent Sialyl-Le x (sLe x ) (also known as CD15s) is observed (15,(22)(23)(24). The absence of sLe a antigen expression on quiescent mucosa contrasts with its reversible expression in regenerative mucosa and its persistent expression in dysplasia (22).…”
Section: Introductionmentioning
confidence: 99%